Women's Knowledge of and Support for Abortion Restrictions in Texas: Findings from a Statewide Representative Survey. Issue 4 (15th April 2016) - White, Kari; Potter, Joseph E.; Stevenson, Amanda J.; Fuentes, Liza; Hopkins, Kristine; Grossman, Daniel
Abstract : CONTEXT: States have passed numerous laws restricting abortion, and Texas passed some of the most restrictive legislation between 2011 and 2013. Information about women's awareness of and support for the laws' provisions could inform future debates regarding abortion legislation. METHODS: Between December 2014 and January 2015, some 779 women aged 18–49 participated in an online, statewide representative survey about recent abortion laws in Texas. Poisson regression analysis was used to assess correlates of support for a law that would make obtaining an abortion more difficult. Women's knowledge of specific abortion restrictions in Texas and reasons for supporting these laws were also assessed. RESULTS: Overall, 31% of respondents would support a law making it more difficult to obtain an abortion. Foreign‐born Latinas were more likely than whites to support such a law (prevalence ratio, 1.5), and conservative Republicans were more likely than moderates and Independents to do so (2.3). Thirty‐six percent of respondents were not very aware of recent Texas laws, and 19% had never heard of them. Among women with any awareness of the laws, 19% supported the requirements; 42% of these individuals said this was because such laws would make abortion safer. CONCLUSIONS: Many Texas women of reproductive age are unaware of statewide abortion restrictions, and some support these requirements because of misperceptions about the safety of abortion. Advocates and policymakers should address these knowledge gaps in efforts to protect access to legal abortion.